A novel diarylethene-based fluorescent "turn-on" sensor for the selective detection of Mg2+. Issue 11 (19th February 2019) - Wang, Zhen; Cui, Shiqiang; Qiu, Shouyu; Pu, Shouzhi
Abstract : A new photochromic diarylethene derivative with a 4-methylphenol unit has been designed and synthesized. Abstract : A new photochromic diarylethene derivative with a 4-methylphenol unit has been designed and synthesized. It displayed distinct photochromism and fluorescent ''turn on'' features to Mg 2+ in acetonitrile solution. With the addition of Mg 2+, there was an obvious increase of fluorescent emission intensity at 552 nm, accompanied by a clear change of fluorescent color from dark purple to green. Meantime, the 1 : 1 stoichiometry between the derivative and Mg 2+ was verified by Job's plot and HRMS. Furthermore, the sensor was successfully applied in the detection of Mg 2+ in practical samples. Moreover, based on the multiple-responsive fluorescence switching behaviors, it also could be used to construct a molecular logic circuit with UV/vis lights and Mg 2+ /EDTA as input signals and the emission at 552 nm as the output signal.